The Development of Students’ Worksheet Based on Inquiry Integrated by Youtube Video as the Alternative of Teaching Materials During the Covid-19 Pandemic Period - Aurora Ade Raysha; Nurrizki Shafira; Auliana Rizky; Ratu Fazlia Inda Rahmayani (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
This research aims to develop students' worksheets based on inquiry integrated by Youtube Video. This is Research and Development (R&D) with the ADDIE model where 50 active students from the Faculty of Teacher Training and Education of Universitas Syiah Kuala are involved at the implementation stage. The results showed that the average percentage of students' worksheets validated by the 3 validators could be categorized as very valid to be used. Questionnaire results showed the students agree that the worksheets developed help with learning during COVID-19, the worksheets help students to study independently, and they easily understand the material presented. Based on the results of validation and students' questionnaire response, it can be concluded that the students' worksheets based on inquiry integrated by youtube videos are feasible to be used the alternative of teaching materials for online learning during the COVID-19 pandemic.